Success in small and medium-scale enterprises : evidence from colombia - "Cortes , Mariluz" (New York, 1987)
Although the extent to which small-scale manufacturing generates employment has been increasingly recognized, most of the research on small enterprises has focused on the smallest units (those with less than 5 workers), which make up the informal sector. The next size larger (those with 5-99 workers), which we refer to as small and medium -size enterprises, has received far less attention.Yet both theoretical considerations and the little empirical evidence reported in the literature suggest that such enterprises are often economically efficient as well as labor intensive, and that they have a significant role in achieving the rapid growth of both output and employment.
Keywords: Samll business colombia